Enacting Border Governance through Multi-scalar Violence: Exclusion and discrimination of Rohingya people in Rakhine state. (9th March 2022) - YONI, NYANA
Abstract: While international focus has been on armed violence and Rohingya refugee flows from Rakhine state, this article pays attention to the myriad forms of 'everyday discrimination' that Muslim Rohingya people have experienced over a prolonged time. These forms of discrimination were observed by the author and reported by Rohingya informants in three areas of Rakhine state during research conducted in 2015. The article argues that systemic discrimination against Rohingya people can be understood as the violent enactment of bordering processes by both state and non-state actors at multiple scales, thus contributing to border governance. Bordering processes can be observed at the national level through the construction of citizenship in law and documentation; at the sub-national level through the restriction of travel and mobility at the township and village levels in Rakhine state; at the household level through household registrations and the control of births, marriages, and family relationships; as well as at the individual level through arrests, detention, and acts of violence. The border is enacted through such processes, with Rohingya people treated as an embodiment of both a political boundary between Myanmar and Bangladesh, and a social boundary constructing the Muslims as 'fearsome and disgusting others' by the country's non-Rohingya groups, particularly by the majority Bamar Buddhist population.